Pregunta
upstudy study bank question image url

Consider the quadratic equation shown below: \[ 2 x=x^{2}+11 \] Determine the coefficients \( a, b \), and \( c \) corresponding to the quadratic formula: \[ \begin{array}{l} a=1 \\ b=-2 \\ c=11 \end{array} \] Now enter those coefficients into the quadratic formula below: \[ x=\frac{-\square \pm \sqrt{(\square)^{2}-4 \cdot \square \cdot \square}}{2 \cdot \square} \]

Ask by Lane Little. in the United States
Feb 26,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The coefficients are: - \( a = 1 \) - \( b = -2 \) - \( c = 11 \) Plugging these into the quadratic formula: \[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot 11}}{2 \cdot 1} \]

Solución

To solve the quadratic equation \( 2x = x^2 + 11 \), we first need to rearrange it into the standard form \( ax^2 + bx + c = 0 \). 1. Rearranging the equation: \[ x^2 - 2x + 11 = 0 \] From this equation, we can identify the coefficients: - \( a = 1 \) - \( b = -2 \) - \( c = 11 \) Now, we can substitute these coefficients into the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Substituting the values of \( a \), \( b \), and \( c \): \[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot 11}}{2 \cdot 1} \] This simplifies to: \[ x = \frac{2 \pm \sqrt{4 - 44}}{2} \] \[ x = \frac{2 \pm \sqrt{-40}}{2} \] Since the discriminant (\( b^2 - 4ac \)) is negative, this indicates that the solutions will be complex numbers. Now, we can express the final form of the quadratic formula with the coefficients filled in: \[ x = \frac{-(-2) \pm \sqrt{(-2)^{2}-4 \cdot 1 \cdot 11}}{2 \cdot 1} \] Thus, the coefficients \( a, b, c \) are: - \( a = 1 \) - \( b = -2 \) - \( c = 11 \)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

First, let's rearrange the given equation \(2x = x^2 + 11\) into standard form. By moving all terms to one side, we get: \[ x^2 - 2x + 11 = 0 \] From this, we see that the coefficients correspond to: \[ a = 1, \quad b = -2, \quad c = 11 \] Now, let's plug these coefficients into the quadratic formula: \[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot 11}}{2 \cdot 1} \] This simplifies to: \[ x = \frac{2 \pm \sqrt{4 - 44}}{2} \] Oh, but wait—it looks like we’ve got a negative number under the square root, leading us to imaginary solutions! So be prepared for some fun with complex numbers! And voila! Now we can fill in the blanks of the quadratic formula provided: \[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot 11}}{2 \cdot 1} \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad